Un método para determinar un grupo de observaciones influyentes en la SCE al ajustar modelos de rango completo (2010)
Throughout this paper is presented a method that allows us to identify the presence of an inﬂuential group of observations for the RSS after ﬁtting a linear model of full rank. Over the residual analysis a Qi statistic is used and the criteria is built, using the distribution of the statistic mentioned under the assumption than ei ∼ N(0;σ2) and Cov(ei,ej) = 0 if (i 6= j).